2009
DOI: 10.2478/v10001-009-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

Aggression at the workplace — psychological consequences of abusive encounter with coworkers and clients

Abstract: Objectives: The aim of the study was to evaluate the consequences of the exposure to workplace aggression from coworkers and clients. Materials and Methods: Participants belonged to two professional groups: nurses (N = 1163) and public service workers (N = 391). Aggression from coworkers and clients/patients was analysed separately. Several multiple regression models were tested to assess the effect of work-related aggression experienced by the subjects on their job satisfaction, professional functioning and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 12 publications
2
52
0
2
Order By: Relevance
“…13 In Poland and Turkey also demonstrated that workplace violence increases the prevalence of psychological conditions such as anxiety and depression among exposed employees. 21,22 Consequently, the physician-patient relationship should be improved by the implementation of several measures, some of them are already implemented in Saudi Arabia such as including introducing malpractice insurance for physicians.…”
Section: Discussionmentioning
confidence: 99%
“…13 In Poland and Turkey also demonstrated that workplace violence increases the prevalence of psychological conditions such as anxiety and depression among exposed employees. 21,22 Consequently, the physician-patient relationship should be improved by the implementation of several measures, some of them are already implemented in Saudi Arabia such as including introducing malpractice insurance for physicians.…”
Section: Discussionmentioning
confidence: 99%
“…35 Merecz, et al detected significant relationship between exposure to violence by patients or fellow workers and burnout levels in their study which they carried out on nurses and social service personnel (EE, DP and reduced PA). 36 Winstanley and Whittington, participated by 375 health care professionals, found that those exposed to violence or threatening multiple times had higher EE and DP levels than those who never experienced such exposure. 37 In our study, residents exposed to daily violence had lower JS grades than those experienced violence on a monthly basis.…”
Section: -26mentioning
confidence: 99%
“…Aggression affects not only the functioning of individual workers but also the efficiency of the entire organization. Occupational exposure to aggressive behaviours is associated with an increased level of stress which, in turn, affects the workers' ability to execute their duties [3].…”
Section: Introductionmentioning
confidence: 99%